2018
DOI: 10.1038/s41598-018-35343-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surface chemistry on the kinetics and thermodynamics of bacterial adhesion

Abstract: This work is concerned with investigating the effect of substrate hydrophobicity and zeta potential on the dynamics and kinetics of the initial stages of bacterial adhesion. For this purpose, bacterial pathogens Staphylococcus aureus and Escherichia coli O157:H7 were inoculated on the substrates coated with thin thiol layers (i.e., 1-octanethiol, 1-decanethiol, 1-octadecanethiol, 16-mercaptohexadecanoic acid, and 2-aminoethanethiol hydrochloride) with varying hydrophobicity and surface potential. The time-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(137 citation statements)
references
References 104 publications
(87 reference statements)
7
129
0
1
Order By: Relevance
“…In addition, the Rsk and Rsk values obtained were consistent with the topography studies performed on different types of surfaces reported in the literature [67][68][69]. The roughness of biomaterial at the nanometric level was also analyzed due to the implications for human cell and bacterial adhesion [62,63]. In bone cells, nanoscale morphology has been used to control cell growth inducing bone tissue formation, bone recovery, and even osseointegration [61,64].…”
Section: Characterization Of the Composite Materialssupporting
confidence: 80%
See 3 more Smart Citations
“…In addition, the Rsk and Rsk values obtained were consistent with the topography studies performed on different types of surfaces reported in the literature [67][68][69]. The roughness of biomaterial at the nanometric level was also analyzed due to the implications for human cell and bacterial adhesion [62,63]. In bone cells, nanoscale morphology has been used to control cell growth inducing bone tissue formation, bone recovery, and even osseointegration [61,64].…”
Section: Characterization Of the Composite Materialssupporting
confidence: 80%
“…Surface chemistry is essential for bacterial and cell adhesion, as it is widely reported that by decreasing the hydrophobicity of the surface, the adhesion of S. aureus can also be decreased [61][62][63][64][65][66]. By incorporating 10% wt of TrGO particles into the PCL polymer matrix, the hydrophobicity of the material decreased significantly from an average value of 113.3 ± 10 • to 74.8 ± 9 • (Figure 6a).…”
Section: Characterization Of the Composite Materialsmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, the competitive interplay of electrostatic and vdW interactions in the anti‐fouling action of the coating has received little attention. This is quite surprising given several previous investigations on the effect of Derjaguin‐Landau‐Verwey‐Overbeek (DLVO) forces on bacterial adhesion to different surfaces [16–18]. In our model, the microorganism is simplistically represented as a charged lipid bilayer encapsulated vesicle‐like system (Fig.…”
Section: Introductionmentioning
confidence: 96%